Status of Atlantic halibut (Hippoglossus hippoglossus) aquaculture production technology in Chile - Pablo Gallardo; Guilherme Wolff Bueno; Cristian Araneda; Tillmann Benfey (Aquaculture Reports, 2022)
The European aquaculture industry began to undertake Atlantic halibut (Hippoglossus hippoglossus) aquaculture in the 1980s due to the favorable growth rate and high market value of this cold-water marine fish. Atlantic halibut cultivation began in Chile in 1996 in the Magallanes region (53˚S). Chilean aquaculture facilities were finally equipped to begin rearing Atlantic halibut after 12 years and a total investment of $ 2 million USD. Infrastructure is now in place to manage the entire production cycle, including broodstock rearing, egg incubation, larval rearing (yolk-sac stage, first-feeding), weaning, the nursery stage, on-growing in land-based tanks, harvest, and marketing. The hatchery phase to produce 10-g juveniles requires 10–12 months, followed by an approximately 30-month grow-out phase in land-based tanks to produce 3-kg fish. Further research and development are being performed in nutrition (diet formulation), genetics (selection for disease resistance and growth rate), fish health, and environmental issues to support the development of a sustainable marine aquaculture industry for this species.